Candidate SNPs for carcass and meat traits in Nelore animals and in their crosses with Bos taurus - Curi, Rogério Abdallah; Krauskopf, Monique Marcondes; Hadlich, Janaína Conte; Fortes, Marina Rufino Salinas; Vankan, Dianne Margaret; Silva, Josineudson Augusto II Vasconcelos; de Oliveira, Henrique Nunes; da Mota, Marcílio Dias Silveira (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the effects of single‑nucleotide polymorphisms (SNPs) in the genes IGF1 (AF_017143.1:g.198C>T), MSTN (AF_320998.1:g.433C>A), MYOD1 (NC_007313:g.1274A>G) and MYF5 (NC_007303:g.1911A>G) on carcass and meat traits in Nelore (Bos indicus) and Nelore x B. taurus. A total of 300 animals were genotyped and phenotyped for rib eye area (REA), backfat thickness (BT), intramuscular fat (IF), shear force (SF) and myofibrillar fragmentation index (MFI). The effects of allele substitution for each SNP were estimated by regression of the evaluated phenotypes on the number of copies of a particular allele using the general linear model. The polymorphism at IGF1 was non‑informative in Nelore animals. In crossbred animals, the IGF1 C allele was associated with greater REA. However, this relation was not significant after Bonferroni correction for multiple testing. The A allele of the MSTN polymorphism was absent in Nelore cattle and was only found in two crossbred animals. The polymorphisms of MYOD1 and MYF5 were little informative in Nelore animals with G allele frequency of 0.097 and A allele frequency of 0.031, respectively. These markers show no association with the analyzed traits in the total sample of evaluated animals